EMPOWERMENT OF FARMER GROUPS IN AN EFFORT TO INCREASE HOUSEHOLD HORTICULTURAL FOOD SECURITY IN ALUE AMBANG-TEUNOM,ACEH JAYA - Wita Ardita; Keumala Fadhiela ND (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2023)
Food security is a condition in which all household have physical and economic access to obtain food for all family members, where households are not at risk of losing both accesses. Due to the conversion of agricultural land into residential land due to the tsunami in 2004, the people of Alue Ambang Village had to fulfill their food needs, especially vegetables, by supplying food from outside tuhe village. Farmer groups can be formed as an effort to increase productivity through joint farming management. This study aims to empower farmer groups in an effort to improve food security in Alue Ambang Village, Teunom District, Aceh Jaya Regency. The research method used in this study is a qualitative research method using a descriptive approach which is carried out by observation, interviews, and documentation, using the technique of determining informants and purposive sampling locations. The total population in this study was 15 people and 5 people were used as samples. The results of the research show that the empowerment of farmer groups is by utilizing the land house yards help the community and farmer groups to meet their household food needs from farmimg. The running of the farmer group must have the support of various related parties such as the head of the farmer group, members of the farmer group and community leaders.